X‐linked inhibitor of apoptosis protein represents a promising therapeutic target for relapsed/refractory ALL. Issue 1 (23rd November 2022) - Carlet, Michela; Schmelz, Karin; Vergalli, Jenny; Herold, Tobias; Senft, Daniela; Jurinovic, Vindi; Hoffmann, Thomas; Proba, Jutta; Weichert, Nina; Junghanß, Christian; Roth, Mareike; Eschenburg, Georg; et al.
Abstract: Acute lymphoblastic leukemia (ALL) represents the most frequent malignancy in children, and relapse/refractory (r/r) disease is difficult to treat, both in children and adults. In search for novel treatment options against r/r ALL, we studied inhibitor of apoptosis proteins (IAP) and Smac mimetics (SM). SM‐sensitized r/r ALL cells towards conventional chemotherapy, even upon resistance against SM alone. The combination of SM and chemotherapy‐induced cell death via caspases and PARP, but independent from cIAP‐1/2, RIPK1, TNFα or NF‐κB. Instead, XIAP was identified to mediate SM effects. Molecular manipulation of XIAP in vivo using microRNA‐30 flanked shRNA expression in cell lines and patient‐derived xenograft (PDX) models of r/r ALL mimicked SM effects and intermediate XIAP knockdown‐sensitized r/r ALL cells towards chemotherapy‐induced apoptosis. Interestingly, upon strong XIAP knockdown, PDX r/r ALL cells were outcompeted in vivo, even in the absence of chemotherapy. Our results indicate a yet unknown essential function of XIAP in r/r ALL and reveal XIAP as a promising therapeutic target for r/r ALL. Synopsis: Smac mimetics sensitize relapsed/refractory acute leukemia (r/r ALL) cell lines towards chemotherapy, independently from TNFα, RIPK1, NFκB and cIAP1/2 signaling. Knockdown in PDX models shows that XIAP harbors an essential function in vivo and represents an important therapeutic target for r/r ALL. r/r ALL cell lines are sensitized to standard chemotherapy by co‐treatment with Smac mimetics (SM). TNFα, RIPK1, NFκB and cIAP1/2 are dispensable for apoptosis induced by the combination of SM and conventional chemotherapy in r/r ALL. To study the role of XIAP in vivo, a miR30‐based, fluorochrome‐guided system was established, with distinct promoters inducing different knockdown strengths. Moderate XIAP knockdown mimics the effects of SM and sensitizes r/r ALL to chemotherapy, making XIAP an interesting therapeutic target to enhance chemotherapy. In PDX models in vivo, strong XIAP knockdown alone reduces ALL growth, demonstrating that XIAP harbors an essential function and represents an interesting therapeutic target in r/r ALL. Abstract : Smac mimetics sensitize relapsed/refractory acute leukemia (r/r ALL) cell lines towards chemotherapy, independently from TNFα, RIPK1, NFκB and cIAP1/2 signaling. Knockdown in PDX models shows that XIAP harbors an essential function in vivo and represents an important therapeutic target for r/r ALL.